Criminalization and capture strategies in the HIV/AIDS assemblage. Issue 4 (17th August 2020) - Rinaldi, Jen; Marques, Olga
Abstract : Purpose: This study aims to ask how HIV/AIDS is arranged as a public threat in and through Canadian law, particularly in relation to transmission, and how strategies of capture extend the affective force of criminalization leading to poor health outcomes for persons living with HIV/AIDS. Design/methodology/approach: This is a conceptual paper with a focus on applying affect theorist Jasbir Puar's work on assemblage and debility. The authors use Puar's work to frame the conditions that persons with HIV/AIDS experience in the Canadian criminal justice context as debilitating. Findings: The authors found that while HIV transmission is not itself a criminal act in the Canadian criminal justice context, activities where transmission is prevalent or possible have been criminalized, particularly in relation to nondisclosure of health status, sex work and substance use. Further, the authors found that when the activities associated with HIV transmission are criminalized, strategies of capture extend the affective force of criminalization first in the inadequate provision of health-care and pharma-care services, second in state resistance to implement harm reduction measure and third in punitive population management strategies. Originality/value: Persons living with HIV/AIDS have historically experienced stigmatization, especially intersecting with neoliberal, white supremacist and heteropatriarchal axes of power. This paper uses assemblage theory to shore up how these relations operate in ways that close off possibilities, by constituting the HIV/AIDS assemblage as a criminal – rather than a health phenomenon. This paper, thus, holds Canada to account for debilitating a historically disadvantaged and multiplying marginalized population.